Cardiovascular disease risk in long‐term breast cancer survivors: A population‐based cohort study. Issue 14 (13th May 2022) - Koric, Alzina; Chang, Chun‐Pin; Mark, Bayarmaa; Rowe, Kerry; Snyder, John; Dodson, Mark; Deshmukh, Vikrant G.; Newman, Michael G.; Fraser, Alison M.; Smith, Ken R.; Date, Ankita P.; Gren, Lisa H.; et al.
Abstract : Background: Breast cancer survival is increasing, making late effects such as cardiovascular disease (CVD) more relevant. The purpose of this study was to evaluate incident CVD following breast cancer diagnosis among long‐term survivors and to investigate possible risk factors for CVD. Methods: A population‐based cohort of 6641 breast cancer survivors diagnosed between 1997 and 2009 who survived at least 10 years was identified within the Utah Cancer Registry. In addition, 36, 612 cancer‐free women from the general population, matched by birth year and state, were identified within the Utah Population Database. Cox proportional hazards models were used to calculate CVD hazard ratios (HRs) for >10 to 15 and >15 years. Results: Long‐term breast cancer survivors had an increased risk of newly diagnosed diseases of the circulatory system (HR, 1.32; 99% confidence interval [CI], 1.00‐1.75) from 10 to 15 years following cancer diagnosis compared with the general population. No increased CVD risks were observed after 15 years. Breast cancer survivors with Charlson Comorbidity Index score ≥2 had a significantly higher risk of diseases of the circulatory system (HR, 2.64; 95% CI, 1.08‐6.45) beyond 10 years following breast cancer diagnosis. Similarly, older age, obesity, lower education, and family history of CVD and breast cancer were risk factors for heart and circulatory system diseases among long‐term breast cancer survivors. Conclusion: Risk of CVD compared to the general population was moderate among this cohort of long‐term breast cancer survivors between 10 to 15 years since cancer diagnosis. Awareness of CVD risks is important for breast cancer survivors. Abstract : The risk of cardiovascular diseases (CVD) between 10 to 15 years since cancer diagnosis was moderate among this cohort of long‐term breast cancer survivors compared to the general population. Awareness of CVD risks is important for breast cancer survivors.